2014
DOI: 10.1105/tpc.114.124446
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membranes Are Subcompartmentalized into a Plethora of Coexisting and Diverse Microdomains inArabidopsisandNicotiana benthamiana   

Abstract: Eukaryotic plasma membranes are highly compartmentalized structures. So far, only a few individual proteins that function in a wide range of cellular processes have been shown to segregate into microdomains. However, the biological roles of most microdomain-associated proteins are unknown. Here, we investigated the heterogeneity of distinct microdomains and the complexity of their coexistence. This diversity was determined in living cells of intact multicellular tissues using 20 different marker proteins from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
183
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(213 citation statements)
references
References 54 publications
13
183
1
Order By: Relevance
“…4A). Our data are in agreement with work by Jarsch et al (2014), who reported the formation of PM subdomains in N. benthamiana and Arabidopsis. As expected, GFP-IQD25 fluorescence colocalized upon plasmolysis with the PM and not with the cell wall, which were stained with FM4-64 and propidium iodide (PI), respectively (Fig.…”
Section: A Subset Of Iqd Proteins Localizes To Distinct Pm Subdomainssupporting
confidence: 83%
See 3 more Smart Citations
“…4A). Our data are in agreement with work by Jarsch et al (2014), who reported the formation of PM subdomains in N. benthamiana and Arabidopsis. As expected, GFP-IQD25 fluorescence colocalized upon plasmolysis with the PM and not with the cell wall, which were stained with FM4-64 and propidium iodide (PI), respectively (Fig.…”
Section: A Subset Of Iqd Proteins Localizes To Distinct Pm Subdomainssupporting
confidence: 83%
“…3). Similar patterns have been reported for Rem proteins (Raffaele et al, 2007;Jarsch et al, 2014), and targeting of AtRem6.6 to subdomains in the PM proved to be sensitive to MTdepolymerizing drugs , as was the case for IQD12 and IQD22 (Fig. 3).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Plant plasma membrane domains have been visualized in vivo using sterol-dependent proteins of the Remorin family [1,2]. The Remorin gene family is unique to plants, found in angiosperms, gymnosperms and bryophytes [3].…”
Section: Introductionmentioning
confidence: 99%